Parrot bornavirus in naturally infected Brazilian captive parrots: Challenges in viral spread control - Silva, Aila Solimar Gonçalves (PLoS One, 2020)
Psittaciform orthobornaviruses are currently considered to be a major threat to the psittacine bird population worldwide. Parrot bornavirus (PaBV) was identified recently in Brazil and, since then, few studies have been conducted to understand the epidemiology of PaBV in captive psittacine birds. In the present study, natural infections by PaBV in South American parrots were investigated in two breeding facilities: commercial (A) and conservationist (B). Thirty-eight psittacine of 21 different species were presented for postmortem examination. Tissue samples were collected and investigated for the presence of PaBV-RNA using RT-PCR. In addition, clinical information about these birds was used when available. PaBV infection was detected in 73.7% of all birds investigated, indicating a wide dissemination of this virus in both facilities. From birds investigated in aviary A, 66.7% showed clinical signs, 100% had typical lesions of proventricular dilatation disease (PDD), 100% had mild to severe proventricular dilatation and 88.9% were PaBV-positive. In birds from aviary B, 27.6% showed clinical signs, 65.5% had typical lesions of PDD, 62% had mild to severe proventricular dilatation and 69% were PaBV-positive. Neurological disease was observed more frequently than gastrointestinal disease. Sequencing analysis of the matrix gene fragment revealed the occurrence of genotype 4 (PaBV-4) in both places. About 15.8% of birds in this study are threatened species. We discussed the difficulties and challenges for controlling viral spread in these aviaries and implications for South American psittacine conservation. These results emphasize the urgent need to develop a national regulatory and health standard for breeding psittacine birds in the country.